Nikolay Karamzin’s History in Fyodor Dostoevsky’s Novel The Idiot - Nikolay N. Podosokorsky (Достоевский и мировая культура: Филологический журнал, 2024)
The article explores the influence of Nikolay Karamzin’s History of the Russian State (1818–1829) on Fyodor Dostoevsky’s novel The Idiot (1868–1869). Karamzin’s historical and literary work significantly shaped Dostoevsky’s worldview from childhood and remained highly valued by him in adulthood. Dostoevsky owned a copy of Karamzin’s multi-volume work in his library and, according to acquaintances, knew it “almost by heart.” The article demonstrates that the mention of Karamzin’s History in the opening scene of The Idiot should be understood in the context of the heightened public interest in Karamzin during the centenary of his birth, celebrated in Russia in December 1866. This interest persisted during the years when The Idiot was written and published. Karamzin was regarded by several Russian writers and public figures in the late 1860s, including critic Nikolay Strakhov, who was close to Dostoevsky at that time, as a moral guide for contemporaries and as an ideal of a “beautiful man.” This image resonates with that of Prince Lev Myshkin, to whom the know-it-all official Lukyan Lebedev advises immersing oneself in Karamzin’s History. The article also clarifies and supplements previous research on the connection between Dostoevsky’s The Idiot and Karamzin’s History. Special attention is given to comparing The Idiot with Karamzin’s autobiographical novel A Knight of Our Time (1802–1803), whose main character, like Dostoevsky’s hero, is named Leon and shares Don Quixote-like qualities.